Molecular Mechanisms of Hepatitis C Virus (HCV) Triggering Normal Cell Transformation into Cancer: A Mini Review - Dhea Kharisma, Viol; Sima, Putri Melati (Generasi Biologi Indonesia, 2023)
Hepatitis C virus (HCV) infection has become a serious concern because it can trigger the severity of complications leading to hepatocellular carcinoma (HCC). HCV is a virus with single-stranded RNA (ssRNA) type genetic material, with virions composed of structural proteins such as glycoprotein, envelope, and core, then HCV also has nonstructural proteins such as NS3, NS4, NS4B, NS5A, NS5B. The development of HCV infection therapy has been carried out through direct-acting antiviral agents (DAAs) with the hope of achieving a reduction in mortality and HCC risk. However, these strategies cannot fully reduce the risk of HCC in patients who have recovered from HCV infection. This review briefly reviews several factors from the virus and host to trigger cellular transformation of hepatocytes into HCC. HCV infection can trigger the transformation of hepatocytes into cancer in the case of HCC influenced by two factors consisting of pro-oncogenic and growth factors. Pro-oncogenic of HCV initiates HCC through the release of ROS that triggers genetic mutations and upregulation of proliferation in hepatocytes, it allows internal cell factors to also work in the process of transformation into cancer such as increased growth factor activity for antiapoptotic response, survival, and proliferation to trigger increased severity of HCC.